Cause-specific mortality for 240 causes in China during 1990–2013: a systematic subnational analysis for the Global Burden of Disease Study 2013. Issue 10015 (16th January 2016) - Zhou, Maigeng; Wang, Haidong; Zhu, Jun; Chen, Wanqing; Wang, Linhong; Liu, Shiwei; Li, Yichong; Wang, Lijun; Liu, Yunning; Yin, Peng; Liu, Jiangmei; Yu, Shicheng; et al.
Summary: Background: China has experienced a remarkable epidemiological and demographic transition during the past three decades. Far less is known about this transition at the subnational level. Timely and accurate assessment of the provincial burden of disease is needed for evidence-based priority setting at the local level in China. Methods: Following the methods of the Global Burden of Disease Study 2013 (GBD 2013), we have systematically analysed all available demographic and epidemiological data sources for China at the provincial level. We developed methods to aggregate county-level surveillance data to inform provincial-level analysis, and we used local data to develop specific garbage code redistribution procedures for China. We assessed levels of and trends in all-cause mortality, causes of death, and years of life lost (YLL) in all 33 province-level administrative units in mainland China, all of which we refer to as provinces, for the years between 1990 and 2013. Findings: All provinces in mainland China have made substantial strides to improve life expectancy at birth between 1990 and 2013. Increases ranged from 4·0 years in Hebei province to 14·2 years in Tibet. Improvements in female life expectancy exceeded those in male life expectancy in all provinces except Shanghai, Macao, and Hong Kong. We saw significant heterogeneity among provinces in life expectancy at birth and probability of death at ages 0–14, 15–49, and 50–74 years. Such heterogeneity is also present in cause of death structures between sexes and provinces. From 1990 to 2013, leading causes of YLLs changed substantially. In 1990, 16 of 33 provinces had lower respiratory infections or preterm birth complications as the leading causes of YLLs. 15 provinces had cerebrovascular disease and two (Hong Kong and Macao) had ischaemic heart disease. By 2013, 27 provinces had cerebrovascular disease as the leading cause, five had ischaemic heart disease, and one had lung cancer (Hong Kong). Road injuries have become a top ten cause of death in all provinces in mainland China. The most common non-communicable diseases, including ischaemic heart disease, stroke, chronic obstructive pulmonary disease, and cancers (liver, stomach, and lung), contributed much more to YLLs in 2013 compared with 1990. Interpretation: Rapid transitions are occurring across China, but the leading health problems and the challenges imposed on the health system by epidemiological and demographic change differ between groups of Chinese provinces. Localised health policies need to be implemented to tackle the diverse challenges faced by local health-care systems. Funding: China National Science & Technology Pillar Program 2013 (2013BAI04B02) and Bill & Melinda Gates Foundation.